2020
DOI: 10.1155/2020/2768403
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of the Mode of Action of Viola odorata in Diabetes

Abstract: Background. The metabolic syndrome increases the risk of different diseases such as type 2 diabetes. The prevalence of metabolic syndrome has rapidly grown and affected more than 230 million people worldwide. Viola odorata is a traditionally used plant for the treatment of diabetes; however, its mechanism to manage diabetes is still unknown. Purpose. This study was designed to systematically assess the mechanism of action of Viola odorata in diabetes. Methods. An extensive literature search was made to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Modern studies have found that TP53, RB1, CCNB1 and CDKN1A have anti-diabetic activity. [ 39 , 40 ] Studies have found that CCND1 plays a role in obesity-related T2DM, which is related to its participation in fatty acid and glucose metabolic pathways and oxidation/reduction reactions [ 41 ] ; while CDK4/6 has a regulatory effect on human beta cell proliferation. [ 42 ] Studies have found that CDK1 is the key to drive oxidative phosphorylation, and the abnormal increase in the secretion of oxidative phosphorylation components may be the basis for the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Modern studies have found that TP53, RB1, CCNB1 and CDKN1A have anti-diabetic activity. [ 39 , 40 ] Studies have found that CCND1 plays a role in obesity-related T2DM, which is related to its participation in fatty acid and glucose metabolic pathways and oxidation/reduction reactions [ 41 ] ; while CDK4/6 has a regulatory effect on human beta cell proliferation. [ 42 ] Studies have found that CDK1 is the key to drive oxidative phosphorylation, and the abnormal increase in the secretion of oxidative phosphorylation components may be the basis for the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Docking Study. The docking of ten compounds (Rutin, Aregenal, Astragalin, Baicalien, Copistine, Epiberberine, Hyperin, Kaempferol, Myristic acid, and Palmatine) with one of the targets (interleukin-6) was carried to computationally search an appropriate ligand that fits the binding site of protein-based on its geometry and energy [18].…”
Section: Go and Pathway Enrichmentmentioning
confidence: 99%